Relationship enhancement methods - Cook, Barbara (Encyclopedia of Autism Spectrum Disorders, 2018)
Keywords: dept.cmd

Interpersonal supports - Cook, Barbara (Encyclopedia of Autism Spectrum Disorders, 2018)
Keywords: dept.cmd

Brainstem Audiometry - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Cochlea - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Deafness - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Dichotic Listening - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Hearing - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Otitis Media - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Pediatric Speech Intelligibility Test - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Screening Test for Auditory Processing Disorders - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Peer mentors for students with ASD on college campuses - Cook, Barbara; Weiss, Deborah (Encyclopedia of Autism Spectrum Disorders, 2018)
Keywords: dept.cmd

Differentiating ASD from DLD in toddlers - Paul, Rhea; Chawarska, Katyrzyna; Volkmar, Fred R (Perspectives on Language Learning and Education, 2008)
Keywords: dept.cmd

Deaf-Blind - McCullagh, Jennifer; Weiss, Deborah (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Perception and Production of Prosody by Speakers with Autism Spectrum Disorders. - Paul, Rhea; Augustyn, Amy; Klin, Ami; Volkmar, Fred R (Journal of Autism and Developmental Disorders, 2005)
Speakers with autism spectrum disorders (ASD) show difficulties in suprasegmental aspects of speech production, or prosody, those aspects of speech that accompany words and sentences and create what is commonly called "tone of voice." However, little is known about the perception of prosody, or about the specific aspects of prosodic production that result in the perception of "oddness." The present study examined the perception and production of a range of specific prosodic elements in an experimental protocol involving natural speech among speakers with ASD between 14 and 21 years of age, in comparison with a typical control group. Results revealed ceiling effects limiting interpretation of findings for some aspects of prosody. However, there were significant between-group differences in aspects of stress perception and production. The implications of these findings for understanding prosodic deficits is speakers with autism spectrum disorders, and for future research in this area, are discussed.
Keywords: *Autistic Disorder/co [Complications]; *Language Disorders/et [Etiology]; *Perceptual Disorders/et [Etiology]; *Phonetics; *Speech Disorders/et [Etiology]; *Speech Perception; Adolescent; Adult; Autism; Autistic Disorder; Humans; Language; Language Disorders; Language Disorders/di [Diagnosis]; Language Tests; Male; Perceptual Disorders; Perceptual Disorders/di [Diagnosis]; Phonetics; Prosody; Speech Discrimination Tests; Speech Disorders; Speech Disorders/di [Diagnosis]; Speech Perception; Speech Production Measurement; article; autism; child; clinical article; clinical protocol; controlled study; correlation analysis; dept.cmd; human; intelligence quotient; intermethod comparison; language; medical assessment; peer-reviewed; perception; priority journal; prosody; reliability; scoring system; speech; speech disorder; statistical significance; stress; task performance

Babysitter training guide for families with individuals with ASD - Bean, K; Neers, K; Cook, Barbara; Eren, R (Encyclopedia of Autism Spectrum Disorders, 2020)
The Second Edition of this major reference work expands its coverage and continues to break new ground as an electronic resource for students, educators, researchers, and professionals. Comprehensive in breath and textbook in depth, the Second Edition of the Encyclopedia of Autism Spectrum Disorders serves as a reference repository of knowledge in the field as well as a regularly updated conduit of new knowledge long before such information trickles down from research to standard textbooks. The Second Edition of the Encyclopedia digests and presents new and updated information for readers who need to stay current with the latest research and clinical practices, including advances in neurobiology and genetics, diagnostic instruments and assessment tests, pharmaceutical treatments, and behavioral, speech and language, and other rehabilitative therapies. The Second Edition of the Encyclopedia covers topics across the following major conceptual areas of ASD and PDDs, including: Research trends and findings Behavior/speech Communication TreatmentsEducation Taking advantage of the techniques offered by the electronic medium, the Second Edition of the Encyclopedia of Autism Spectrum Disorders offers an extensive cross-referencing system facilitating search and retrieval of information. This unique, comprehensive Second Edition of the Encyclopedia of Autism Spectrum Disorders is an essential reference for advanced undergraduate and graduate students as well as researchers, professors, clinicians, and other practitioners across such related disciplines as developmental psychology, child and adolescent psychiatry, social work, child and school psychology, behavioral therapy, and sociology of education.
Keywords: dept.cmd

Production of syllable stress in speakers with autism spectrum disorders - Paul, Rhea; Bianchi, Nancy; Augustyn, Amy; Klin, Ami; Volkmar, Fred R. (Research in Autism Spectrum Disorders, 2008)
This paper reports a study of the ability to reproduce stress in a nonsense syllable imitation task by adolescent speakers with autism spectrum disorders (ASD), as compared to typically developing (TD) age-mates. Results are reported for both raters' judgments of the subjects' stress production, as well as acoustic measures of pitch range and duration during stressed and unstressed syllable production. Results reveal small but significant differences between speakers with ASD and typical speakers in both perceptual ratings of stress and instrumental measures of duration of syllables. The implications of these findings for understanding prosodic deficits in ASD are discussed. (C) 2007 Elsevier Ltd. All fights reserved.
Keywords: Autism; Prosody; Syllable stress; acoustics; adolescent; adult; article; autism; clinical article; controlled study; dept.cmd; feedback system; female; human; intelligence quotient; male; mental task; motor coordination; pitch; priority journal; school child; speech articulation; speech perception; task performance

Speech and prosody characteristics of adolescents and adults with high-functioning autism and asperger syndrome - Shriberg, Lawrence D.; Paul, Rhea; McSweeny, Jane L.; Klin, Ami; Cohen, Donald J.; Volkmar, Fred R. (Journal of Speech Language and Hearing Research, 2001)
Speech and prosody-voice profiles for 15 male speakers with High-Functioning Autism (HFA) and 15 male speakers with Asperger syndrome (AS) were compared to one another and to profiles for 53 typically developing male speakers in the same 10- to 50-years age range. Compared to the typically developing speakers, significantly more participants in both the HFA and AS groups had residual articulation distortion errors, uncodable utterances due to discourse constraints, and utterances coded as inappropriate in the domains of phrasing, stress, and resonance. Speakers with AS were significantly more voluble than speakers with HFA, but otherwise there were few statistically significant differences between the two groups of speakers with pervasive developmental disorders. Discussion focuses on perceptual-motor and social sources of differences in the prosody-voice findings for individuals with Pervasive Developmental Disorders as compared with findings for typical speakers, including comment on the grammatical, pragmatic, and affective aspects of prosody.
Keywords: dept.cmd